Analysis of Indonesian Tourism Potentials Through the Sustainable Tourism Perspective in the New Normal Era - Yamin, Muhammad; Darmawan, Arif; Rosyadi, Slamet (Universitas Muhammadiyah Yogyakarta, 2021)
This article is part of an international relations study conducted by the authors. This study aims to illustrate the extent to which Indonesia can get out of the â€œentanglementâ€ of the COVID-19 pandemic, especially in the tourism industry sector. Another purpose of writing this article is to analyze the Indonesian governmentâ€™s role in using the term â€œnew normalâ€ and its relation to sustainable tourism during the COVID-19 pandemic has not ended. Tourism during the COVID-19 pandemic is the focus of the discussion of this article because it is one of the industries most harmed by this pandemic. Globally the loss of world tourism reaches US22 billion. This figure will continue to increase as long as this pandemic cannot be controlled through vaccines and drugs. No exception for Indonesia, which lost the countryâ€™s original income from this sector, reaching tens of trillions of rupiah in just four months since WHO announced COVID-19 as a global pandemic. The new normal situation during the ongoing COVID-19 pandemic is an opportunity as well as a challenge for world tourism in general and Indonesian tourism in particular. The change in lifestyle and habits of the community in traveling directly or indirectly has â€œhitâ€ this industry very hard. Undeniably, reactivating tourism industry activities do have considerable risk, but on the other hand, many sectors depend on this industry. Cleanliness, Health, Safety, Environment Sustainability (CHSE) strategy conducted by the Indonesian government is one of the efforts in re-mobilizing Indonesiaâ€™s tourism sector amid the COVID-19 pandemic, as well as the opportunity to apply three main principles of sustainable tourism in the new normal era, namely involving the social sector in policy engagement, maintaining the sustainability of natural resources and making sustainable development a synonym of economic growth.